PENCEGAHAN STUNTING PADA BALITA - Dwi Astuti; Yunus Mustaqim; Ummi Kulsum; Yunita Rusida; Anwari Anwari; Eka Kurniawati; Muhammad Khoirurrosyid (Jurnal Abdimas Indonesia, 2022)
Abstract Stunting is one of the nutritional problems experienced by toddlers in the world. More than half of the world's stunting toddlers were in Asia (55%) and another third (39%) were in Africa in 2017. The highest number of stunting cases in South Asia is 58.7% and the lowest in Central Asia is 0.9%. Based on the World Health Organization (WHO), Indonesia is the country with the third highest number of stunting cases in Southeast Asia, with an average of 36.4%. This service activity was carried out in Papringan Village for Cadre mothers by providing briefings on the meaning of stunting, the causes of stunting, stunting prevention, early detection of stunting toddlers and the impact of stunting on toddlers. The expected results in this devotion are modules on free sex behavior for adolescents, stker on the red flags of free skes behavior.